How Mood and Task Complexity Affect Children's Recognition of Others' Emotions. Issue 1 (3rd June 2013) - Cummings, Andrew J.; Rennels, Jennifer L.
Abstract Previous studies examined how mood affects children's accuracy in matching emotional expressions and labels (label‐based tasks). This study was the first to assess how induced mood (positive, neutral, or negative) influenced five‐ to eight‐year‐olds' accuracy and reaction time using both context‐based tasks, which required inferring a character's emotion from a vignette, and label‐based tasks. Both tasks required choosing one of four facial expressions to respond. Children responded more accurately to label‐based questions relative to context‐based questions at the age of five to seven, but showed no differences at the age of eight, and when the emotional expression being identified was happiness, sadness, or surprise, but not disgust. For the context‐based questions, children were more accurate at inferring sad and disgusted emotions compared with happy and surprised emotions. Induced positive mood facilitated five‐year‐olds' processing (decreased reaction time) in both tasks compared with induced negative and neutral moods. Results demonstrate how task type and children's mood influence children's emotion processing at different ages.